Poučevanje spoznavanja okolja in naravoslovni kapital učencev - Kožuh, Vasja (Revija za elementarno izobraževanje, 2020)
Teaching early science and pupil’s natural science capital. This paper presents in detail the results of research in which the primary interest was teaching early science in the 1st trimester of elementary school. It was concluded that, in terms of popularity, expressed by the teacher’s own estimation of their competence to teach a specific course, the introduction to environmental science falls a little above average. With regard to the frequency of carrying out various activities, it was established that teachers employ the following activities less than others: connecting, interpreting, organising and analysing data by carrying out simple research and using ICT and e-learning. Teachers prefer to assess the students’ knowledge with the evaluation method rather than with other assessment methods.
Keywords: natural science; scientific knowledge; scientific skills; methods of teaching; assessment of knowledge